PERAN MATA KULIAH EKONOMI KOPERASI UNTUK MENUMBUHKAN KARAKTER DAN MINAT BERKOPERASI MAHASISWA PRODI MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIMOR - Ghawa Rado, Bernadus (AKSIOMA : Jurnal Manajemen, 2022)
This article is a study on Cooperative Economics education which aims to examine more deeply the role of cooperative economic education in fostering cooperative character and interest in Management Study Program students, Faculty of Economics and Business, Unimor. The results of this study discuss the role of cooperative economics courses for students of the Management Study Program, Faculty of Business Economics, Unimor where this cooperative economics course is expected to foster character and interest in cooperatives, especially those in Unimor and cooperatives in Kefamenanu. So that the cooperatives in Unimor and in Kefamenanu can provide a role and a forum for the community's economy